FAKTOR PREDIKTOR KEPATUHAN WAJIB PAJAK DALAM PERSPEKTIF THEORY OF PLANNED BEHAVIOR (STUDI EMPIRIS PADA KPP PRATAMA RUTENG) - Jehadun, Maximus; Ng, Suwandi; Daromes, Fransiskus Eduardus (Dinamika Akuntansi Keuangan dan Perbankan, 2024)
This research aims to analyze the predictor factors that influence taxpayer compliance, which are built within the theory of planned behavior model. The research was conducted on individual taxpayers registered at the Pratama Ruteng Tax Service Office, which is within the working area of the East Nusa Tenggara Regional Office of the Directorate General of Taxes. Data collection was conducted through a survey. Data analysis was performed using regression with the SPSS application. The results indicate that both taxpayer morality and tax justice perception have a positive and significant impact on taxpayer compliance. Conversely, tax complexity has a negative and insignificant effect on taxpayer compliance. These findings imply that taxpayer compliance behavior is greatly determined by the experiences and conditions of the taxpayer, particularly concerning aspects of morality, justice perception, and tax complexity.